Dampak Putusan Mahkamah Konstitusi Terhadap Dinamika Politik dan Kepercayaan Publik di Indonesia: Analisis Implikasi Hukum dan Etika - Kansil, Christine S.T; Putri Meilika Nadilatasya (UNES Law Review, 2024)
The Constitutional Court is one of the judicial power institutions appointed to carry out judicial functions to uphold the law and justice as fair as possible. According to Law Number 24 of 2003, the Constitutional Court has the duty and function to handle constitutional cases relating to certain constitutional issues. To ensure that the constitution is implemented responsibly in accordance with the will of the people and the principles of democracy, constitutional judges must have knowledge and skills in state administration as well as a commitment to implement and oversee public life. The Constitutional Court's decision on the age limit of presidential and vice-presidential candidates in Law No. 7/2017 on General Elections (Election Law) is considered a measure of the qualifications of a leader, and this decision has caused much debate in society. The purpose of this research is to identify how the Constitutional Court's decision impacts Indonesian politics as well as the ethical standards violated by the judges when making the decision.